Lipoprotein(a) concentrations, apolipoprotein(a) isoforms and clinical endpoints in haemodialysis patients with type 2 diabetes mellitus: results from the 4D Study - Kollerits, Barbara; März, Winfried; Ritz, Eberhard (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. High lipoprotein(a) [Lp(a)] concentrations and low molecular weight (LMW) apolipoprotein(a) [apo(a)] isoforms are associated with cardiovas